Spatio-temporal and cumulative effects of land use-land cover and climate change on two ecosystem services in the Colombian Andes (2019)
Climate change can have marked effects on ecosystem service (ES) provision in the Andes, particularly in peri-urban areas. In addition to global-change related processes, cumulative effects such as changing socio-political dynamics, environmental policies, and conflicts are also changing type and magnitude of land use–land cover (LULC) dynamics in the Colombian Andes. Studies in the region have investigated the effects of LULC change, deforestation and extreme climatic events on the hydrology of watersheds and carbon sequestration. Yet, less is known on how the cumulative effects of climate and LULC changes will drive water yield and carbon sequestration. To investigate these cumulative effects, we study two different watersheds near Bogota, Colombia and their ES for the period 2016–2046. We use IPCC-LULC scenarios, expert elicitation, hydro-meteorological data, and integrated modelling using temporal LULC change and ESs valuation models to parse out effects of LULC versus climate change on two representative ESs. Our results show forest and shrublands remain stable during the analysis period. However, urban conversion of agricultural pastures is substantial. We found that climate change scenarios had greater effect on water yield and supply than LULC scenarios in both watersheds. However, carbon sequestration was greater in rural forest and shrubland areas farther from Bogota. In contrast to current land use zoning being promoted by local elected officials, our findings indicate that land-use development and policies in near-urban basins need to minimize urbanization in agriculture and pasture LULCs, as these can have substantial effects on water yield. Similarly, land use polices in ex-urban areas need to conserve forested and shrubland areas to maximize their carbon offset potential. Collectively, our results highlight the need to incorporate climate change conditions in decision making and land use planning processes, in order to maintain the capacity of ecosystems, both urban and rural, to provide services to society. © 2019 Elsevier B.V.